Postoperative analgesia in children when using clonidine or fentanyl with ropivacaine given caudally - Usha Shukla; T Prabhakar; Kiran Malhotra (Wolters Kluwer Medknow Publications, 2011)
Background: The aim of the study was to compare the efficacy of clonidine and fentanyl as an additive to ropivacaine given via single shot caudal epidural in pediatric patients for postoperative pain relief. Materials and Methods: In the present double blind study, 90 children of ASA-I-II aged 3-8 years scheduled for infraumblical surgical procedures were randomly allocated to two groups to receive either ropivacaine 0.25% 1 ml/kg+clonidine 2 μg/kg (group I) or ropivacaine 0.25% 1 μl/kg+fentanyl 1 μg/kg (group II). Caudal block was performed after the induction of general anesthesia. Postoperatively patients were observed for analgesia, sedation, hemodynamics, and side effects/complications. Results: Both the groups were similar with respect to patient and various block characteristics. The analgesic properties and hemodynamics were also comparable in both groups (P > 0.05). Side effects such as respiratory depression, vomiting bradycardia were significantly less in group I than group II (P < 0.05) ensuing more patient comfort. Conclusions: The analgesic properties of clonidine and fentanyl as additives to ropivacaine in single shot caudal epidural in children are comparable but clonidine offers a more favorable side effect profile. The use of clonidine as additive to ropivacaine in caudal epidural is superior choice to fentanyl because of lack of unwanted side effects and increased patient comfort.